Cushing’s syndrome caused by ACTH precursors secreted from a pancreatic yolk sac tumor in an adult—a case report and literature review - Chang, Johnny Yau Cheung; Woo, Chariene Shao Lin; Chow, Wing Sun; White, Anne; Wong, Ka Chung; Tsui, Po; Lee, Alan Chun Hong; Leung, Eunice Ka Hong; Woo, Yu Cho; Tan, Kathryn Choon Beng; Lam, Karen Siu Ling; Lee, Chi Ho; et al. (Frontiers in Medicine, 2023)
Here we report the first adult case of pancreatic yolk sac tumor with ectopic adrenocorticotropic hormone (ACTH) syndrome. The patient was a 27-year-old woman presenting with abdominal distension, Cushingoid features, and hyperpigmentation. Endogenous Cushing's syndrome was biochemically confirmed. ACTH level was in the normal range which raised the suspicion of ACTH precursor-dependent disease. Elevated ACTH precursors were detected, supporting the diagnosis of ectopic ACTH syndrome. Functional imaging followed by tissue sampling revealed a pancreatic yolk sac tumor. The final diagnosis was Cushing's syndrome due to a yolk sac tumor. The patient received a steroidogenesis inhibitor and subsequently bilateral adrenalectomy for control of hypercortisolism. Her yolk sac tumor was treated with chemotherapy and targeted therapy. Cushing's syndrome secondary to a yolk sac tumor is extremely rare. This case illustrated the utility of ACTH precursors measurement in confirming an ACTH-related pathology and distinguishing an ectopic from a pituitary source for Cushing's syndrome.